2008
DOI: 10.1002/jmv.21176
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for cytomegalovirus reactivation in cytomegalovirus‐seropositive kidney‐transplant patients

Abstract: The aims of the present study were to assess the incidence of cytomegalovirus (CMV) reactivation, and to determine the predictive factors for CMV reactivation in CMV seropositive kidney-transplant patients. One hundred ninety CMV seropositive kidney-transplant patients were included in this study; of these, 39 patients had received CMV prophylaxis. CMV DNAemia was assessed by real-timepolymerase chain reaction assay every 2 weeks until day 120, then every 3-4 weeks until day 180, and then every month until day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…This is in accordance with previous publications that demonstrated a higher risk of CMV infection or CMV disease with a maintenance immunosuppression containing ciclosporine A [18,19]. Additionally, we have found that donor HCMV-seropositivity is an independent risk factor for HCMV reactivation after kidney transplantation in HCMV-seropositive patients [22].…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous publications that demonstrated a higher risk of CMV infection or CMV disease with a maintenance immunosuppression containing ciclosporine A [18,19]. Additionally, we have found that donor HCMV-seropositivity is an independent risk factor for HCMV reactivation after kidney transplantation in HCMV-seropositive patients [22].…”
Section: Discussionsupporting
confidence: 93%
“…In pediatric lung transplant, the impact of adding CMVIG to standard antiviral prophylaxis has not been previously explored. The risks for CMV infection and disease in this cohort are similar to those reported previously in both the adult and pediatric literature, with increased risk during the early transplant era and with donor/recipient CMV seropositivity [5,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 83%
“…In pediatric lung transplant, the impact of adding CMVIG to standard antiviral prophylaxis has not been previously explored. The risks for CMV infection and disease in this cohort are similar to those reported previously in both the adult and pediatric literature, with increased risk during the early transplant era and with donor/recipient CMV seropositivity [5, 2023]. …”
Section: Discussionsupporting
confidence: 81%